2022
DOI: 10.1093/mnras/stac3729
|View full text |Cite
|
Sign up to set email alerts
|

The obscured nucleus and shocked environment of VV 114E revealed by JWST/MIRI spectroscopy

Abstract: Compact Obscured Nuclei (CONs) potentially hide extreme supermassive black hole (SMBH) growth behind large column densities of gas/dust. We present a spectroscopic analysis of the heavily obscured nucleus and the surrounding environment of the eastern region of the nearby (z = 0.02007) interacting galaxy VV 114 with the JWST Mid-InfraRed Instrument (MIRI). We model the spectrum from 4.9 - 28 μm to extract Polycyclic Aromatic Hydrocarbon (PAH) emission and the underlying obscured continuum. We find that the NE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
5
2
Order By: Relevance
“…Although Iono et al (2013) identified the NE core as potentially harboring an AGN due to the enhanced HCN/HCO + ratio, an analysis of X-ray and millimeter data by Privon et al (2020) showed that in fact the HCN/HCO+ is not a robust indicator of total AGN luminosity or its fractional contribution to IR luminosity. Our findings regarding the nature of the two bright cores in VV 114E are not in agreement with the analysis of JWST MIRI data by Donnan et al (2023) who Values measured with Spitzer/IRS for ULIRGs and LIRGs from the GOALS sample are plotted as "+" symbols, with VV 114E and three comparative ULIRGs denoted with red diamonds (Stierwalt et al 2013). The starburst galaxy M82 is shown as a blue square (Spoon et al 2007).…”
Section: Evidence For Agn Activitycontrasting
confidence: 80%
“…Although Iono et al (2013) identified the NE core as potentially harboring an AGN due to the enhanced HCN/HCO + ratio, an analysis of X-ray and millimeter data by Privon et al (2020) showed that in fact the HCN/HCO+ is not a robust indicator of total AGN luminosity or its fractional contribution to IR luminosity. Our findings regarding the nature of the two bright cores in VV 114E are not in agreement with the analysis of JWST MIRI data by Donnan et al (2023) who Values measured with Spitzer/IRS for ULIRGs and LIRGs from the GOALS sample are plotted as "+" symbols, with VV 114E and three comparative ULIRGs denoted with red diamonds (Stierwalt et al 2013). The starburst galaxy M82 is shown as a blue square (Spoon et al 2007).…”
Section: Evidence For Agn Activitycontrasting
confidence: 80%
“…This number exceeds the value derived from the depth of the 9.7 μm silicate absorption feature (Donnan et al 2023, their Figures 4 and A1) by less than a factor of 2. With the corrected column density for SF-NE, the relative depths of the 9.7 μm silicate feature for SF-NE and SF-SW are also reproduced.…”
Section: Cocontrasting
confidence: 56%
“…However, even then, collisional excitation will be irrelevant, since at such high densities the gas temperature will equal the dust temperature, which is set by the local radiation field. Mapping of the [Fe II] 5.34 μm emission line has revealed the presence of a large-scale bow shock covering the SF-SW region (Donnan et al 2023). It is of interest to consider the possible role of this shock for the excitation of the molecular gas in SF-SW, since C-type shocks in molecular clouds can easily produce postshock temperatures of several times 10 3 K without dissociating the molecules (Draine et al 1983).…”
Section: Collisional Excitationmentioning
confidence: 99%
“…In Figure 10 we show the excitation diagrams for the different regions in the nucleus of M83. As noted by Donnan et al (2023), the S(3) transition at 9.665 μm is found at the peak of the silicate absorption, and therefore highly sensitive to extinction. In the analysis by Donnan et al (2023), they include this line with We show with a gray line the best model fit adopting the parameters listed in Table 4.…”
Section: Appendixmentioning
confidence: 78%